Saturday

August 23, 2014

August 23, 2014

Posted by **Bailey** on Saturday, January 12, 2008 at 3:01pm.

You just solve for g...

- Pre- Algebra -
**Damon**, Saturday, January 12, 2008 at 3:36pmI am going to assume that you mean:

(-1/7) g + (5/6) g = 9

(-6/42) g + (35/42) g = 9

(29/42)g = 9

29 g = 9*42

g = 9*42/29

**Related Questions**

Pre-Algebra - How do you solve this Pre-Algebra problem: $1.25x + $2.25y = $916 ...

Pre- Algebra - 4(x-2)=3(1.5+x) Use Dis.Property Combine like terms Solve using ...

Algebra 2 - How do I answer this f(x) = x - 3 (x + 4)^(1/2) and am asked how to ...

pre-algebra - Solve the inequality- j-7<24 8+b<-3 h/4>16 Treat the ...

pre-algebra - write an inequality for the sentence. The total t is greater than ...

pre-algebra - Solve the inequality- a/3>4 -2n<10 p/(-2)<-5 Trreat the ...

Pre-Algebra - I don't understand this equation: Given f(x)=4(x)+1 find the value...

Pre algebra - How do I solve Quadratic equations by factoring? (for example how ...

pre-algebra - kk my teach told me to describe and draw things that are about pre...

pre-algebra - 7x-12=x+2+2x-3x Solve for x Combine the terms on the right hand ...